THE PRACTICE OF FAMILY PRAYER TRADITIONS IN THE GMIM EBEN HAEZER KAATEN CONGREGATION: Praktik Tradisi Doa dalam Keluarga di Jemaat GMIM Eben Haezar Kaaten - Iren Takasiliang; Madeline D. A. Tamaka; Nadia M. C. Sinubu; Patricia Putri Reppi; Denny Adry Tarumingi; Mieke Nova Sendow; Evi Stans Evlin Tumiwa; Maria Elisa Tulangow (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Abstract This article describes family prayer traditions as practiced in the GMIM Eben Haezer Kaaten congregation as a place of spiritual growth, cultural inculturation, and pastoral care. Based on a qualitative and participatory ethnographic design comprising 15 nuclear families, in-depth interviews, participant observation, and the use of supporting documentation, this study examines how family prayer has been structured, organised, and experienced in the day-to-day life of Minahasan Christian families. The results demonstrate that family prayer has continued to be actively incorporated into the daily life of the family, particularly in the evenings or at mealtimes or even during crises, in such a way that the home is an ecclesia domestica where faith is recounted and passed down through generations. Prayer leadership is shared in differentiated forms: fathers are expected to be the spiritual heads, mothers to be consistent guardians, and children to be emerging leaders who are given responsibilities. The study also indicates that Minahasan cultural values, including mapalus, walewangko, and masarang, inform the sense of prayer and the dynamics of relations, which is transformed into a place of thankfulness, vulnerability, and solidarity. Meanwhile, the study notes that there are strong stressors, including work exhaustion, school pressure, information-related disruptions, and relationship stressors, that jeopardise the status quo of this tradition. The study finds that the reinforcement of family prayer must be carried out through purposeful pastoral accompaniment, ecclesial practices, and theological understanding of domestic spirituality as a location of Christian witness in modern Minahasa.